Toward Controlled Morphology of Fecu Nanoparticles: Cu Concentration and Size Effects - Baltazar-Rojas, S; Arancibia-Miranda, N; Arancibia-Miranda, N; Allende-Prieto, S; Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P; Rojas-Núñez, J (American Chemical Society, 2018)
Bimetallic nanoparticles (NPs) can be tailored by varying the concentration of their constituent elements, resulting in novel structures and/or configurations, leading to interesting electronic, mechanical, and chemical properties. In this paper, by means of molecular dynamics calculations, we study the morphology of bimetallic FeCu NPs as a function of the Cu concentration. Our results evidence a core-shell (CS) structure for low Cu concentrations and a Janus (JN)-like morphology for high Cu content. Structural and energy characterizations were performed to determine the atomic-scale behavior of the NPs. Using a continuous model to describe immiscible components, we obtain a stability transition curve between CS and JN-like structures for several NP sizes and concentrations. Results from both methods are compared with experimental data obtained for NPs with low and high Cu content, evidencing a good agreement among the three approaches. © 2018 American Chemical Society.